Gaya gaya si Poca! a cartoon face animation application Pocahontas edition - Gabas, Reggie Mae T.; Gatdula, Emily D.; Pudadera, George G.; Satuito, Arlene A. (2003)
Before, the creation of a cartoon animation requires extensive knowledge in sketching, painting and other skills common in the field of fine arts. Artists and cartoonists have to go through the rigorous task of drawing every single frame of the output video to simulate movement in the cartoon's face features such as the eyes, eyebrows, the nose and the mouth. In so doing, artists have to give more attention to details in the movement of the cartoon's face features in order to create a smooth transition between video frames and to show a perfect animation as the cartoon mimics actual human face feature movements. The burden does not end here. Animators need to keep track of huge amount of cartoon sketches and arrange these in a specified sequence to create the animation, while the same set of procedures is repeated for every single cartoon character included in the movie.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Animation (Cinematography); Image processing -- Digital techniques -- Software; Human face recognition (Computer science); Gaya gaya si Poca!.